Data acquisition and process control using personal computers - Ozkul, Tarik (Marcel Dekker, 1996)
Covers all areas of computer-based data acquisition--from basic concepts to the most recent technical developments--without the burden of long theoretical derivations and proofs. Offers practical, solution-oriented design examples and real-life case studies in each chapter and furnishes valuable selection guides for specific types of hardware.